Carbon translocation from a plant to an insect-pathogenic endophytic fungus - Scott W. Behie (Nature Portfolio, 2017)
The endophytic fungusMetarhizium robertsiiis also an insect pathogen and can facilitate transfer of insect-derived nitrogen to host plants. Here, the authors show that carbon is transferred from plant to fungus suggesting a tripartite interaction where nitrogen is exchanged for photosynthate.